Protein Purification Protocols - Paul Cutler (Methods in Molecular Biology Volume 244)
General Strategies. Preparation of Extracts From Animal Tissues. Extraction of Recombinant Protein From Bacteria. Protein Extraction From Fungi. Subcellular Fractionation of Animal Tissues. Subcellular Fractionation of Plant Tissues: Isolation of Plastids and Mitochondria. The Extractionof Enzymes From Plant Tissues Rich in Phenolic Compounds. Avoidance of Proteolysis in Extracts. Making and Changing Buffers. Purification and Concentration by Ultrafilñtration. bulk Purification by Fractional Precipitation. Ion-Exchange Chomatography. Affinity Chomatography. Lectin Affinity Chromatography. Immunoaffinity Chromatography. Chromatography on Hydroxyapatite. Thiophilic Affinity Chromatography and Related Methods. Affinity Precipitation Methods. Osielectric Focusing. Chromatofocusing. Size-Exclusion Chromatography. Reversed-Phase Chromatography of Proteins. Extraction of Membrane Proteins. Extraction of Dtergent From Protein Fractions. Purification of Membrane Proteins. Lyophilization of Proteins. Storage of Pure Proteins. Electroelution of proteins from Polyacrylamide Gels. Electroblotting of proteins From Polyacrylamide Gels. Two-Dimensional Polyacrylamide Gel Electrophoresis for Proteome Analyses. Microscale Solution Isoelectrofocusing: A Sample Prefractionation Method for Comprehensive Proteome Analysis. Practical Column Chromatography. Dtection Methods. Peptide Proteomics. Multidimensional Liquid Chromatography of Proteins. Mass Spectrometry. Purification of Therapeutic Proteins. Purification Process Scale-Up.